2021
DOI: 10.1186/s12917-021-02884-z
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and genotyping of Staphylococcus aureus obtained from food animals in Sichuan Province, China

Abstract: Background Staphylococcus aureus (S. aureus), especially methicillin-resistant Staphylococcus aureus (MRSA), is considered a common zoonotic pathogen, causing severe infections. The objective of this study was to investigate the antimicrobial susceptibility, resistance genes and molecular epidemiology among MRSA and methicillin-susceptible Staphylococcus aureus (MSSA) isolated from food animals in Sichuan Province, China. Methods This study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…A gene encoding macrolides–lincosamides–streptogramin resistance ( ermC ) and rep10 were identified in plasmid pE5 circulating in three isolates: S1, S14, and S23. These results indicate that these isolates have acquired these genes from others via plasmids, which is in accordance with previous studies [ 58 , 59 ]. Horizontal transfer of the ermC gene in a small plasmid was commonly documented in animal and human staphylococcal species [ 59 ].…”
Section: Resultssupporting
confidence: 93%
“…A gene encoding macrolides–lincosamides–streptogramin resistance ( ermC ) and rep10 were identified in plasmid pE5 circulating in three isolates: S1, S14, and S23. These results indicate that these isolates have acquired these genes from others via plasmids, which is in accordance with previous studies [ 58 , 59 ]. Horizontal transfer of the ermC gene in a small plasmid was commonly documented in animal and human staphylococcal species [ 59 ].…”
Section: Resultssupporting
confidence: 93%
“…The ermB gene in this research is comparable to a study reported in Isfahan, Iran, where only 22.2% of ermB genes were detected [48], while our result was lower than that found in Sichuan Province, China, food animals [49]. In addition to ermA, ermC, and ermF, ermB is the most prominent gene in staphylococci that significantly contributes to macrolide, lincosamide, and streptogramin B antibiotics [50].…”
Section: Introductionsupporting
confidence: 72%
“…In recent decades, the unwise use of antibiotics culminated into spread of resistant S. aureus isolates, especially MRSA. Worryingly, isolates with diminished susceptibility to vancomycin have been described worldwide and are associated with unfavorable prognosis 20 . Though both linezolid and tedizolid were approved for management of S. aureus infections worldwide, no much data have been published from Egypt in this context.…”
Section: Discussionmentioning
confidence: 99%